1995
DOI: 10.1523/jneurosci.15-07-05004.1995
|View full text |Cite
|
Sign up to set email alerts
|

The Shaker-like potassium channels of the mouse rod bipolar cell and their contributions to the membrane current

Abstract: RT PCR on mRNA from enzymatically dissociated, isolated bipolar cells showed that these neurons express the Shaker-like K+ channels Kv1.1, Kv1.2, and Kv1.3. Immunohistochemical localization showed each channel to have a unique subcellular distribution: Kv1.1 immunoreactivity was detected in the dendrites and axons terminal, whereas Kv1.2 and Kv1.3 subunits were localized to the axon and the postsynaptic membrane of the rod ribbon synapse, respectively. Whole-cell patch-clamp recordings indicated that the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
2
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 54 publications
5
48
2
4
Order By: Relevance
“…Therefore, the present study utilized this model system for the analysis of IP 3 R-driven Ca 2+ signaling and confirmed the maintenance of sub-cellular protein distributions related to this pathway [8,[10][11][12][13]57]. Previous reports that describe the presence of progesterone receptors [57] as well as genomic steroid hormone receptor activity in the retina [80] corroborate our results of progesterone receptor immunoreactivity and function in the present paper. Kobrinsky and colleagues had shown that reduced levels of IP 3 R protein decrease progesterone-mediated cellular activity in a model system of oocyte maturation [81].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, the present study utilized this model system for the analysis of IP 3 R-driven Ca 2+ signaling and confirmed the maintenance of sub-cellular protein distributions related to this pathway [8,[10][11][12][13]57]. Previous reports that describe the presence of progesterone receptors [57] as well as genomic steroid hormone receptor activity in the retina [80] corroborate our results of progesterone receptor immunoreactivity and function in the present paper. Kobrinsky and colleagues had shown that reduced levels of IP 3 R protein decrease progesterone-mediated cellular activity in a model system of oocyte maturation [81].…”
Section: Discussionsupporting
confidence: 89%
“…As reported previously, acute enzymatic and mechanical isolation of rod bipolar cells does not affect cellular morphology and key physiological functional properties [13,[56][57][58][59][60][61]. Therefore, the present study utilized this model system for the analysis of IP 3 R-driven Ca 2+ signaling and confirmed the maintenance of sub-cellular protein distributions related to this pathway [8,[10][11][12][13]57].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Tissue localization and the absence of currents other than those generated by homomeric channels argue against certain Kv complexes (30 -32). Thus, the assembly of Kv1.3 with Kv1.1 and Kv1.2 was questioned by immunohistochemical localization in mouse rod bipolar cells (30). In addition, a differential distribution also argues against a heteropolymer between Kv1.1 and Kv1.5 in Schwann cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…Such K ϩ channels are very sensitive to 4-aminopyridine (4AP) and tetraethylammonium (Stü hmer et al, 1989). Calcium-insensitive, delayed rectifiers (I K [V] ) appear to be a general feature of vertebrate retinas, because they have been recorded from a wide variety of retinal neurons, including rod and cone photoreceptors (Attwell and Wilson, 1980;Bader et al, 1982;Barnes and Hille, 1989;Maricq and Korenbrot, 1990), horizontal cells (Tachibana, 1981), bipolar cells (Attwell et al, 1987;Kaneko et al, 1989;Karschin and Wä ssle, 1990;Klumpp et al, 1995a), and ganglion cells (Lipton and Tauck, 1987). ICC localization of ''delayedrectifier'' subunits indicates good general correspondence with the electrophysiological data obtained from rat and mouse retinas (Karschin and Wä ssle, 1990;Hwang et al, 1993;Klumpp et al, 1995a,b).…”
Section: Indexing Terms: Immunocytochemistry; Potassium Channels; Fismentioning
confidence: 99%